1991
DOI: 10.1111/j.1745-459x.1991.tb00499.x
|View full text |Cite
|
Sign up to set email alerts
|

Usage Behavior of Meat Products by Australians and Hong Kong Chinese: A Comparison of Free Choice and Consensus Profiling

Abstract: Australian und Hong Kong Chinese male and female consumers, aged 20 to 30 years, evaluated a range of 16 meat products using two questionnaires. One questionnuire comprised the 12 most frequently used terms by consumers to describe how. when and where they would most ofen consume each product. The alternute questionnuire for each individual comprised free choice vocabu-I a n . Half' of each consumer sample used the consensus questionnaire and the other half: the free choice questiotznaireJirst, and indicated h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1991
1991
2018
2018

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…As an idiographic technique it is particularly suitable in cross-cultural (McCoy, 1983;Scriven and Mak, 1991) and cultural work with Asian consumers (Meudic and Cox, 2001) being free of researcher or semantic bias. In a comparative study of Hong Kong Chinese (studying in Australia) and European-origin Australian students, Scriven and Mak (1991) used RGM (and also conventional descriptive techniques) to look at perceptions of a range of meat products. They found little difference between the two methods but concluded that RGM successfully elicited similar perceptions of the various meat products regardless of culture.…”
Section: Construct Theory and Repertory Grid Methodologymentioning
confidence: 99%
“…As an idiographic technique it is particularly suitable in cross-cultural (McCoy, 1983;Scriven and Mak, 1991) and cultural work with Asian consumers (Meudic and Cox, 2001) being free of researcher or semantic bias. In a comparative study of Hong Kong Chinese (studying in Australia) and European-origin Australian students, Scriven and Mak (1991) used RGM (and also conventional descriptive techniques) to look at perceptions of a range of meat products. They found little difference between the two methods but concluded that RGM successfully elicited similar perceptions of the various meat products regardless of culture.…”
Section: Construct Theory and Repertory Grid Methodologymentioning
confidence: 99%
“…In their paper Scriven and Mak state that they used the Consensus program to perform a Generalized Procrustes Analysis. They say to have used Consensus because "this program is a microprocessor program, which avoids the need for Genstat programming language generally required for generalized Procrustes Analysis" (Scriven and Mak 1991). Their statement is wrong for two reasons:…”
Section: Introductionmentioning
confidence: 99%